Learning the service drills in novice volleyball athletes - Forte, D.; D'Isanto, T.; Di Domenico, F.; Altavilla, G. (Journal of Human Sport & Exercise, 2019)
Volleyball service is the fundamental element with which the game begins; it can be carried out from below, from a floating top, or from above in a jump. This article discusses the changes in speed and accuracy of service as a result of different training methods. A sample of 33 participants with no experience in volleyball was divided into three groups. Two groups carried out three weeks of training, the first following the ecological approach, in complete freedom, the second group following the mixed method (global-analytical-global) while the third group formed the control group. The participants were evaluated in advance and on two successive occasions. In each test, accuracy and speed of service were recorded. The results highlight the improvement in the accuracy and speed of the practice groups. In addition, the mixed training group presented greater consistency in accuracy, decreasing the variable error of their attempts. The main conclusion of the study is that the mixed training methodology can be a very effective method for learning the service in volleyball with inexperienced populations.